Revisiting the looking at nothing phenomenon: Visual and semantic biases in memory search. Issue 3 (15th March 2016) - de Groot, Floor; Huettig, Falk; Olivers, Christian N. L.
ABSTRACT: When visual stimuli remain present during search, people spend more time fixating objects that are semantically or visually related to the target instruction than looking at unrelated objects. Are these semantic and visual biases also observable when participants search within memory? We removed the visual display prior to search while continuously measuring eye movements towards locations previously occupied by objects. The target absent trials contained objects that were either visually or semantically related to the target instruction. When the overall mean proportion of fixation time was considered, we found biases towards the location previously occupied by the target, but failed to find biases towards visually or semantically related objects. However, in two experiments the pattern of biases towards the target over time provided a reliable predictor for biases towards the visually and semantically related objects. We therefore conclude that visual and semantic representations alone can guide eye movements in memory search, but that orienting biases are weak when the stimuli are no longer present.